PENERAPAN FUNGSI-FUNGSI MANAJEMEN DALAM MENINGKATKAN MUTU PENDIDIKAN - ., Syamsuddin (Idaarah: Jurnal Manajemen Pendidikan, 2017)
Improving the quality of education can not be separated from the quality of human resources owned. Therefore, the Education Institution must also be able to meet the human resource needs of both quantity and quality by increasing the educational resources to supply human resource needs in accordance with the demand and improve the local education process by developing the necessary elements and supporting elements. Improving the quality of learning needs to use strategies that can be applied to each institution by taking into account the characteristics of the institution. With qualified human resources, it is hoped that educational institutions will become institutions capable of effectively facing the challenges of the future.